2009
DOI: 10.1097/aog.0b013e318195873e
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Neurodevelopment Impairment in Twin–Twin Transfusion Syndrome Treated With Fetoscopic Laser Surgery

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
113
2
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 120 publications
(119 citation statements)
references
References 25 publications
2
113
2
2
Order By: Relevance
“…Overall, the incidence of NDI was 18% (50/278). Four risk factors were found to be significantly associated with increased risk for NDI: gestational age at laser surgery (odds ratio [OR] 1.30, 95% CI: 1.0-1.7; p = .05), Quintero stage (OR 3.55 for each increment in stage, 95% CI: 1.1-11.8; p = .04), lower gestational age at birth (OR 1.39 for each week, 95% CI 1.1-1.8; p = .01), and lower birth weight (OR 1.18 for each 100-g decrease, 95% CI 1.1-1.3; p = < .01; Lopriore et al, 2009). Gray et al (2011) found a 4% (5/113) incidence of CP and NDI was diagnosed in 12% (14/113) of TTTS survivors.…”
Section: Long-term Neurodevelopmental Outcome In Ttts Treated With Lamentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, the incidence of NDI was 18% (50/278). Four risk factors were found to be significantly associated with increased risk for NDI: gestational age at laser surgery (odds ratio [OR] 1.30, 95% CI: 1.0-1.7; p = .05), Quintero stage (OR 3.55 for each increment in stage, 95% CI: 1.1-11.8; p = .04), lower gestational age at birth (OR 1.39 for each week, 95% CI 1.1-1.8; p = .01), and lower birth weight (OR 1.18 for each 100-g decrease, 95% CI 1.1-1.3; p = < .01; Lopriore et al, 2009). Gray et al (2011) found a 4% (5/113) incidence of CP and NDI was diagnosed in 12% (14/113) of TTTS survivors.…”
Section: Long-term Neurodevelopmental Outcome In Ttts Treated With Lamentioning
confidence: 99%
“…Low gestational age at birth was significantly associated with NDI (relative risk [RR]: 1.20 for each week, 95% CI: 1.1-1.4; p = .02). In 2009, three European fetal therapy centers (Barcelona, Leuven, and Leiden) performed a multicenter follow-up study to investigate risk factors for NDI in TTTS treated with laser (Lopriore et al, 2009). Overall, the incidence of NDI was 18% (50/278).…”
Section: Long-term Neurodevelopmental Outcome In Ttts Treated With Lamentioning
confidence: 99%
See 1 more Smart Citation
“…In our series, the neonatal death rate is about 8%. In other words, our live-birth rate is 8% higher than our neonatal survival rate (8). Not only is there no information on neonatal mortality in that series, also information on neonatal morbidity, a strong predictor of long-term outcome, is lacking.…”
mentioning
confidence: 80%
“…Of surviving infants, 11% have some form of developmental impairment, of which cerebral palsy is the most common, being present in 5% (7). The single most important predictor of impairment is an early gestational age at birth (8). Therefore, at best only 40% of parents will ultimately take home two healthy babies.…”
mentioning
confidence: 99%